Two-Tier Lyme Disease Serology Test Results Can Vary According to the Specific First-Tier Test Used. (22nd February 2019) - Maulden, Alexandra B; Garro, Aris C; Balamuth, Fran; Levas, Michael N; Bennett, Jonathan E; Neville, Desiree N; Branda, John A; Nigrovic, Lise E
Abstract: Background: Variability in 2-tier Lyme disease test results according to the specific first-tier enzyme immunoassay (EIA) in children has not been examined rigorously. In this study, we compared paired results of clinical 2-tier Lyme disease tests to those of the C6 peptide EIA followed by supplemental immunoblotting (C6 2-tier test). Methods: We performed a prospective cohort study of children aged ≥1 to ≤21 years who were undergoing evaluation for Lyme disease in the emergency department at 1 of 6 centers located in regions in which Lyme disease is endemic. The clinical first-tier test and a C6 EIA were performed on the same serum sample with supplemental immunoblotting if the first-tier test result was either positive or equivocal. We compared the results of the paired clinical and C6 2-tier Lyme disease test results using the McNemar test. Results: Of the 1714 children enrolled, we collected a research serum sample from 1584 (92.4%). The clinical 2-tier EIA result was positive in 316 (19.9%) children, and the C6 2-tier test result was positive or equivocal in 295 (18.6%) children. The clinical and C6 2-tier test results disagreed more often than they would have by chance alone ( P = .002). Of the 39 children with either a positive clinical or C6 2-tier test result alone, 2 children had an erythema migrans (EM) lesion, and 29 had symptoms compatible with early disseminated Lyme disease. Conclusions: Two-tier Lyme disease test results differed for a substantial number of children on the basis of the specific first-tier test used. In children for whom there is a high clinical suspicion for Lyme disease and who have an initially negative test result, clinicians should consider retesting for Lyme disease. Abstract : Results of 2-tier Lyme disease tests can differ according to the specific first-tier test used. Clinicians should consider retesting for Lyme disease in children for whom there is a high clinical suspicion and who initially have a negative Lyme disease test result.